The role of fMRI in drug development. Issue 2 (February 2018) - Carmichael, Owen; Schwarz, Adam J.; Chatham, Christopher H.; Scott, David; Turner, Jessica A.; Upadhyay, Jaymin; Coimbra, Alexandre; Goodman, James A.; Baumgartner, Richard; English, Brett A.; Apolzan, John W.; Shankapal, Preetham; et al.
Highlights: Functional MRI continues to have the potential to play a useful role in developing novel compounds. But the lack of consensus on optimal techniques for acquisition and analysis limit its utility. Open questions about the biological basis of fMRI limits the ability to inferences from it. Greater data sharing, information exchange, and research funding could overcome limitations. Abstract : Functional magnetic resonance imaging (fMRI) has been known for over a decade to have the potential to greatly enhance the process of developing novel therapeutic drugs for prevalent health conditions. However, the use of fMRI in drug development continues to be relatively limited because of a variety of technical, biological, and strategic barriers that continue to limit progress. Here, we briefly review the roles that fMRI can have in the drug development process and the requirements it must meet to be useful in this setting. We then provide an update on our current understanding of the strengths and limitations of fMRI as a tool for drug developers and recommend activities to enhance its utility. Teaser: Brain fMRI has the potential to become a powerful tool for clinical trials but is currently underutilized. Here, we explain why and present a path forward.